Is it wrong for doctors to be human? Can resident doctors learn to function with less sleep? - Maan, Arvinder Singh; Sandhu, Kulwinder Singh; Thomas, Oshin; Singh, Jagdeepak (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2020)
Background: Medical residency programs are traditionally supposed to be having long working hours, which can be associated with a poor quality of sleep and resultant daytime sleepiness. This poses threat to both physician and patient. This study has an alarming importance in recent scenario, where India is witnessing growing incidents of assaults against resident doctors. We evaluated the subjective sleep quality, day time sleepiness, satisfaction with life, stress, anxiety and depression and their association with subjective sleep quality amongst the residents on their off-duty days and also compared these findings amongst various departments of our institution. Methods: This cross-sectional study was conducted among 77 first year resident doctors of Government Medical College, Amritsar during the period from May 2018 to March 2019. The tools used for assessment were Pittsburgh sleep quality index, Epworth sleepiness scale, the satisfaction with life scale (SWLS) and depression, anxiety and stress scale-21 questionnaire. Results: Our results indicated that 71.43% residents were poor sleepers. 53.24% residents had day time sleepiness of which 46.75% had excessive day time sleepiness. 40.26% residents had mild to moderate stress, 44.16% had mild to moderate anxiety, 31.16% residents suffered from depression of which 18.18% residents suffered moderate to severe depression. 90.91% residents were satisfied with their life on applying SWLS. Poor sleep quality was perceived greatly by the resident doctors in our public hospital. Conclusions: Understanding the potential impacts of fatigue on resident physicians performance /safety and using this knowledge to optimize shift-duty schedule may reduce the risks to both doctors and patients.